Analysis of ultrasonographic features of adnexal masses and usefulness of application this method in differential diagnosis of adnexal tumors - Fuchs, Tomasz; Pomorski, Michał; Wiatrowski, Artur; Slejman, Nadim; Zimmer, Mariusz (Menopause Review/Przegląd Menopauzalny, 2006)
Introduction: Differential diagnosis of adnexal masses is important problem in contemporary gynecology. Although some new biochemical and biophysical diagnostic method had been introduced, still there is no test which can clearly distinguish benign adnexal mass from malignant one. Aim of the study: The aim of the study was to estimate usefulness of ultrasonographic tumor features as single parameter which allows to distinguish between malignant and benign mass. Materials and methods: 288 patients with presence of adnexal masses were examined in Department of Fertility and Obstetrics, Medical University Wrocław. There were 238 benign adnexal masses and 50 malignant ones. After post-operative pathological verification, usefulness of sonographic features as single parameters was estimated. All patients were examined using Acuson 128XP10 ultrasound scanner with endovaginal probe 7 Mhz. Results: Among single parameters blood flow parameters i.e. low Resistance Index (RI≤0,4) correlated most with presence of malignant masses, data achieved from black &white tumor scan were less useful for differential diagnosis of adnexal masses. Conclusions: 1. Color transvaginal Doppler scan is a very helpful diagnostic tool in differential diagnosis of adnexal masses. 2. Most useful single parameter used as diagnostic tool to discriminate between malignant and benign adnexal masses is RI value. Using it as a single parameter is highly specific. 3. Other adnexal sonographic features are less helpful in clinical practice, although some of them increase risk of malignancy of examined adnexal mass.